The Optimum Equilibrium when Using Experiments in Teaching – Where Virtual and Real Labs Stand in Science and Engineering Teaching Practice - Tsihouridis, Charilaos; Vavougios, Dennis; Batsila, Marianthi; Ioannidis, George (International Journal of Emerging Technologies in Learning (iJET), 2019)
The present study compares the relative merits of virtual and real educational laboratories in science and engineering education, in terms of their educational effectiveness and if they were the most appropriate for learning. The age of the students was also investigates as a possible factor affecting the outcome. The authors of the present paper started by identifying 67 recent and mutually compatible research papers (articles, doctoral theses, and reviews) and reviewed their content performing a meta-study to discover their findings about the most effective laboratory type. Web-based tools were used, such as e-journals, databases, thematic guides, and portals, catalogues of other libraries offered by a variety of universities. A critical analysis followed to compare findings and reach decisions. In a corollary section of the study, the authors conducted some semi-structured discussions with 25 experienced science teachers of secondary, primary and tertiary education, for verification purposes. Discussions followed, all participants being arranged in 5 different groups, focusing on still open topics in need of further clarification. The present two-prong analysis resulted in a number of interesting results, presented herein, on the relative effectiveness of virtual and real laboratories as a factor of student age.